Procedures for a Dawn: Autumn, Winter, Spring - Fedrizzi , Fernanda (Revista do Colóquio, 2025)
Through Procedures for a Dawn: Autumn, Winter, Spring, an essay composed of photographs and graphic elements that expands on the discussion begun in the publication About the days when I dawned here (2025), the artistic production that occurs in the unfolding of procedures defined throughout the work is presented. During the 144 days that the author spent in Swansea, United Kingdom, on a journey that began in Porto Alegre, Brazil, photographs of the view from her bedroom window are recorded, constructing a narrative of the seasons and the passage of time through the landscape. The essay reflects on time and place as constituent elements of a processual making.